Personality, age and sex differences in wild and zoo-housed Japanese macaques, Macaca fuscata - Joléne van der Mescht; Miho Inoue-Murayama; Takafumi Suzumura; Lydia M. Hopper; Bonaventura Majolo; Andrew J.J. MacIntosh; Drew M. Altschul; Alexander Weiss (Animal Behaviour, 2026)

First report of melon and cucumber plants as natural hosts of cowpea mild mottle virus - B. A. Silva; C. M. Kauffmann; S. B. S. Cardenas; P. S. Queiroz; A. M. V. Batista; H. B. S. Mota; A. K. Inoue-Nagata; D. M. S. Freitas; Tatsuya Nagata (Journal of Plant Pathology, 2026)

Modelling free residual chlorine decay in a residential district water distribution network using smart water meter data - S. Obaid; K. Hosoi; N. M. Ngoc; T. Inoue; K. Yokota (International Journal of Environmental Science and Technology, 2025)
Chlorine is the most common disinfectant in drinking water worldwide, and the free residual chlorine concentration has been stipulated at least 0.1 mg/L according to Japanese drinking water standard to ensure disinfection efficacy during distribution. In addition, Japan is also applying approximately 0.4 mg/L chlorine at treatment plants to supply tasty drinkable water to residents. Although a concentration lower than 0.4 mg/L can help avoid an unpleasant chlorine taste in the supply water, it raises challenges for maintaining residual chlorine greater than the standard throughout distribution pipelines. The chlorine concentration decreases along distribution pipes because of bulk decay and wall decay. These decays depend on the initial chlorine concentration, temperature, time, pipe material, etc. Therefore, bottle tests with the Arrhenius theory were set up on the water at the distribution inlet in the Chibata district in Kosai city, Japan at various temperatures and times to measure the bulk decay coefficient. A literature review and root square mean error matching field data were conducted to estimate the wall decay coefficient. These decay coefficients were input into EPANET 2.2 to simulate water quality using smart water meters’ hourly consumption data. Therefore, the points where chlorine concentrations were below the standard could be hourly estimated.

P19-40 Risk assessment of AFB1 due to CYP3A4-mediated biotransformation with a highly sensitive human intestinal model - L. Bai; K. Tachibana; M. Murata; T. Inoue; H. Mizuguchi; S. Maeda; K. Ikemura; M. Okuda; T. Kusakabe; M. Kondoh (Toxicology Letters, 2024)

Hybridization and reticulate evolution in Diphasiastrum (flat-branched clubmosses, Lycopodiaceae) – New data from the island of Taiwan and Vietnam - M. Schnittler; M. Inoue; O.N. Shchepin; J. Fuchs; H. Chang; P. Lamkowski; R. Knapp; K. Horn; H.W. Bennert; M. Bog (Molecular Phylogenetics and Evolution, 2024)

Preliminary analysis focusing on in-vessel thermal hydraulics in loss-of-heat removal systems in a sodium-cooled fast reactor - H. Sonoda; S. Fujita; M. Inoue; T. Okawa (Annals of Nuclear Energy, 2023)

P25-22: Comparison of BMDL calculation performance by the recently developed Bayesian BMD calculation tools using quantal datasets of animal toxicity studies - A. Hirose; Y. Shigeta; T. Kawamura; K. Inoue; M. Matsumoto (Toxicology Letters, 2023)

P03-12: In vivo mutagenicity assessment and derivation of reference dose of styrene - Y. Murata; M. Matsumoto; T. Iso; Y. Shigeta; S. Hasegawa; T. Umano; N. Hirose; K. Horibata; K.-I. Sugiyama; K. Inoue; A. Hirose; K. Masumura (Toxicology Letters, 2023)

Genetic effects of demographic bottleneck and recovery in Kinkazan Island and mainland populations of Japanese macaques (Macaca fuscata) - N. Kazahari; E. Inoue; N. Nakagawa; Y. Kawamoto; T. Uno; M. Inoue-Murayama (Primates, 2023)

Distribution of vasopressin 1a and oxytocin receptor protein and mRNA in the basal forebrain and midbrain of the spiny mouse (Acomys cahirinus) - Jeanne M. Powell; Kiyoshi Inoue; Kelly J. Wallace; Ashley W. Seifert; Larry J. Young; Aubrey M. Kelly (Brain Structure and Function, 2022)

Distribution of brain oxytocin and vasopressin V1a receptors in chimpanzees (Pan troglodytes): comparison with humans and other primate species - Christina N. Rogers Flattery; Daniel J. Coppeto; Kiyoshi Inoue; James K. Rilling; Todd M. Preuss; Larry J. Young (Brain Structure and Function, 2022)

From Surface Water to the Deep Sea: A Review on Factors Affecting the Biodegradation of Spilled Oil in Marine Environment - Hernando Pactao Bacosa; Sheila Mae B. Ancla; Cris Gel Loui A. Arcadio; John Russel A. Dalogdog; Dioniela Mae C. Ellos; Heather Dale A. Hayag; Jiza Gay P. Jarabe; Ahl Jimhar T. Karim; Carl Kenneth P. Navarro; Mae Princess I. Palma; Rodolfo A. Romarate; Kaye M. Similatan; et al. (Journal of Marine Science and Engineering, 2022)
Over the past century, the demand for petroleum products has increased rapidly, leading to higher oil extraction, processing and transportation, which result in numerous oil spills in coastal-marine environments. As the spilled oil can negatively affect the coastal-marine ecosystems, its transport and fates captured a significant interest of the scientific community and regulatory agencies. Typically, the environment has natural mechanisms (e.g., photooxidation, biodegradation, evaporation) to weather/degrade and remove the spilled oil from the environment. Among various oil weathering mechanisms, biodegradation by naturally occurring bacterial populations removes a majority of spilled oil, thus the focus on bioremediation has increased significantly. Helping in the marginal recognition of this promising technique for oil-spill degradation, this paper reviews recently published articles that will help broaden the understanding of the factors affecting biodegradation of spilled oil in coastal-marine environments. The goal of this review is to examine the effects of various environmental variables that contribute to oil degradation in the coastal-marine environments, as well as the factors that influence these processes. Physico-chemical parameters such as temperature, oxygen level, pressure, shoreline energy, salinity, and pH are taken into account. In general, increase in temperature, exposure to sunlight (photooxidation), dissolved oxygen (DO), nutrients (nitrogen, phosphorous and potassium), shoreline energy (physical advection—waves) and diverse hydrocarbon-degrading microorganisms consortium were found to increase spilled oil degradation in marine environments. In contrast, higher initial oil concentration and seawater pressure can lower oil degradation rates. There is limited information on the influences of seawater pH and salinity on oil degradation, thus warranting additional research. This comprehensive review can be used as a guide for bioremediation modeling and mitigating future oil spill pollution in the marine environment by utilizing the bacteria adapted to certain conditions.

Pollution and contamination level of Cu, Cd, and Hg heavy metals in soil and food crop - Ramlan; M. Basir-Cyio; M. Napitupulu; T. Inoue; A. Anshary; Mahfudz; Isrun; M. Rusydi; Golar; Sulbadana; R. Bakri (International Journal of Environmental Science and Technology, 2022)
We aimed to assess and observe the accumulation of Cu, Cd, and Hg heavy metals on land and the contamination of plant tissues in Grand Forest Park, Palu, Indonesia, and its surrounding areas. The method used was a mix between survey and investigation, integrating data on research findings from before 2013 to 2016 with data from 2018. The data were analyzed using a correlation test, and descriptive statistics are presented in the form of tables and graphs. The results show that the highest concentration of Hg was found in the Poboya processing area (575.16 ppm) in 2013, though it gradually decreased to 287.64 ppm in 2018. The results of the Spearman’s rank test at the ∝ 0.05 level between average Cu land and Cu plant concentrations show that the obtained value ( r ) was 0.52 with a rho (ρ) of 0.13, which is not significant ( ρ 0.13 > 0.05), while for Cd and Hg metals, the obtained r values were 0.88 and 0.86, respectively. These two metals showed significant correlations between concentrations of Cd and Hg on land and Cd and Hg in plant tissues (both ρ 0.001 < 0.05). Specifically, the transfer factor (TF) value at the sampling sites of the Grand Forest Park area, Ngatabaru, and PBY from the average of various Hg concentrations in plants was much higher than the TF values of Cu and Cd, specifically being Hg > Cd = Cu or 0.61 > 0.17 = 0.17.

Area-wide insecticide resistance and endosymbiont incidence in the whitefly Bemisia tabaci MEAM1 (B biotype): A Neotropical context - R. A. C. Dângelo; M. Michereff-Filho; A. K. Inoue-Nagata; P. S. da Silva; M. Chediak; R. N. C. Guedes (Ecotoxicology, 2021)

The effects of Nosema ceranae (Microspora: Nosematidae) isolated from wild Apis cerana japonica (Hymenoptera: Apidae) on Apis mellifera - Yuki Hosaka; Yuto Kato; Shinya Hayashi; Madoka Nakai; Seth M. Barribeau; Maki N. Inoue (Applied Entomology and Zoology, 2021)

Biodegradation of binary mixtures of octane with benzene, toluene, ethylbenzene or xylene (BTEX): insights on the potential of Burkholderia, Pseudomonas and Cupriavidus isolates - Hernando P. Bacosa; Jhonamie A. Mabuhay-Omar; Rodulf Anthony T. Balisco; Dawin M. Omar; Chihiro Inoue (World Journal of Microbiology and Biotechnology, 2021)

Expression profile of seven polyamine oxidase genes in rice (Oryza sativa) in response to abiotic stresses, phytohormones and polyamines - G. H. M. Sagor; Masataka Inoue; Tomonobu Kusano; Thomas Berberich (Physiology and Molecular Biology of Plants, 2021)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Complete sequence of a new bipartite begomovirus infecting Sida sp. in Northeastern Brazil - M. A. Macedo; C. M. Rêgo-Machado; M. L. Maliano; M. R. Rojas; A. K. Inoue-Nagata; R. L. Gilbertson (Archives of Virology, 2020)

Complete genome sequence of a new bipartite begomovirus infecting tomato in Brazil - Camila M. Rego-Machado; Erich Y. T. Nakasu; Rosana Blawid; Tatsuya Nagata; Alice K. Inoue-Nagata (Archives of Virology, 2019)

Sources of resistance to Potato virus Y and Pepper yellow mosaic virus in Solanum (section Lycopersicon) germplasm - Renata M. Oliveira; Érico C. Dianese; Mirtes F. Lima; Renato O. Resende; Alice K. Inoue-Nagata; Leonardo S. Boiteux (European Journal of Plant Pathology, 2018)

Characterization of tomato leaf curl purple vein virus, a new monopartite New World begomovirus infecting tomato in Northeast Brazil - M. A. Macedo; L. C. Albuquerque; M. R. Maliano; J. O. Souza; M. R. Rojas; A. K. Inoue-Nagata; R. L. Gilbertson (Archives of Virology, 2018)

Complete genome sequence of melon yellowing-associated virus from melon plants with the severe yellowing disease in Brazil - Thiago M. Costa; Rosana Blawid; Avanor C. da Costa Junior; Mirtes F. Lima; Fernando A. S. de Aragão; Genira P. de Andrade; Gilvan Pio-Ribeiro; Miguel A. Aranda; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2017)

Erratum to: Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

A novel vitivirus-like sequence found in Arracacia xanthorrhiza plants by high throughput sequencing - Layssa M. Oliveira; Anelise F. Orílio; Alice K. Inoue-Nagata; Tatsuya Nagata; Rosana Blawid (Archives of Virology, 2017)

Vulnerability of Community-Based Forest Management to Climate Variability and Extremes: Emerging Insights on the Contribution of REDD+ - Rose Jane J. Peras; Juan M. Pulhin; Makoto Inoue (Small-scale Forestry, 2017)

Factors affecting water availability for high Arctic lichens - T. Inoue; S. Kudoh; M. Uchida; Y. Tanabe; M. Inoue; H. Kanda (Polar Biology, 2017)

Relating food and human hair to assess mercury exposure levels in Poboya, Central Sulawesi, Indonesia - M. M. Sari; T. Inoue; Y. Matsumoto; K. Yokota (International Journal of Environmental Science and Technology, 2017)

Genes, social transmission, but not maternal effects influence responses of wild Japanese macaques (Macaca fuscata) to novel-object and novel-food tests - Coline M. Arnaud; Takafumi Suzumura; Eiji Inoue; Mark J. Adams; Alexander Weiss; Miho Inoue-Murayama (Primates, 2017)

Simultaneous spawning by female stream goby Rhinogobius sp. and the association with brood cannibalism by nesting males - S. Ito; H. Iwao; J. Sakata; M. Inoue; K. Omori; Y. Yanagisawa (Journal of Fish Biology, 2016)
A laboratory experiment was conducted by varying the undersurface area of nesting substratum and the number of females in an experimental tank to elucidate the determinants of the mating pattern in the stream goby, Rhinogobius sp. cross‐band type. Males with larger nests tended to attract two or more females to their nest in a tank. Moreover, males spawned simultaneously with multiple females and entire brood cannibalism by males was rarely observed under a female‐biased sex ratio. When males spawned with a single female with low fecundity, however, entire brood cannibalism occurred at a high frequency, suggesting that a male guarding a nest with fewer eggs consumes the brood. Therefore, spawning behaviour of females that leads to a large egg mass would decrease the risk of entire brood cannibalism. In this species, simultaneous spawning by multiple females in a nest serves as a female counter‐measure against entire brood cannibalism. These results suggest that a conflict of interest between the sexes through brood cannibalism is a major determinant of simultaneous spawning.

Transformation Strategy for Managing Coupled Socio-Ecological Systems: Case Studies from Bangladesh and the Philippines - Abrar Juhar Mohammed; Makoto Inoue; Rose Jane Peras; Tapan Kumar Nath; Mohammed Jashimuddin; Juan M. Pulhin (Small-scale Forestry, 2016)

Review: advances in in situ and satellite phenological observations in Japan - Shin Nagai; Kenlo Nishida Nasahara; Tomoharu Inoue; Taku M. Saitoh; Rikie Suzuki (International Journal of Biometeorology, 2016)
To accurately evaluate the responses of spatial and temporal variation of ecosystem functioning (evapotranspiration and photosynthesis) and services (regulating and cultural services) to the rapid changes caused by global warming, we depend on long-term, continuous, near-surface, and satellite remote sensing of phenology over wide areas. Here, we review such phenological studies in Japan and discuss our current knowledge, problems, and future developments. In contrast with North America and Europe, Japan has been able to evaluate plant phenology along vertical and horizontal gradients within a narrow area because of the country’s high topographic relief. Phenological observation networks that support scientific studies and outreach activities have used near-surface tools such as digital cameras and spectral radiometers. Differences in phenology among ecosystems and tree species have been detected by analyzing the seasonal variation of red, green, and blue digital numbers (RGB values) extracted from phenological images, as well as spectral reflectance and vegetation indices. The relationships between seasonal variations in RGB-derived indices or spectral characteristics and the ecological and CO 2 flux measurement data have been well validated. In contrast, insufficient satellite remote-sensing observations have been conducted because of the coarse spatial resolution of previous datasets, which could not detect the heterogeneous plant phenology that results from Japan’s complex topography and vegetation. To improve Japanese phenological observations, multidisciplinary analysis and evaluation will be needed to link traditional phenological observations with “index trees,” near-surface and satellite remote-sensing observations, “citizen science” (observations by citizens), and results published on the Internet.

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The importance of primary inoculum and area-wide disease management to crop health and food security - A. Bergamin Filho; A. K. Inoue-Nagata; R. B. Bassanezi; J. Belasque; L. Amorim; M. A. Macedo; J. C. Barbosa; L. Willocquet; S. Savary (Food Security, 2016)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Is Recentralization Really Dominant? The Role of Frontline Foresters for Institutional Arrangement in the Philippines - Ayumi Sugimoto; Juan M. Pulhin; Makoto Inoue (Small-scale Forestry, 2014)

A Property-Rights Approach to Understanding Regulations and Practices in Community-Based Forest Management: Comparison of Three Systems in the Philippines - Ei Ei Swe Hlaing; Makoto Inoue; Juan M. Pulhin (Small-scale Forestry, 2013)

The role of the hyporheic zone for a benthic fish in an intermittent river: a refuge, not a graveyard - R. Kawanishi; M. Inoue; R. Dohi; A. Fujii; Y. Miyake (Aquatic Sciences, 2013)

Facing the Challenge of Social Forestry in Japan: The Case of Reviving Harmonious Coexistence Between Forest and People in Okayama Prefecture - Maki Hasegawa; Juan M. Pulhin; Makoto Inoue (Small-scale Forestry, 2013)

Association of root water-uptake ability with drought adaptation in wheat - M. Mori; M. Inagaki; T. Inoue; M. Nachit (Cereal Research Communications, 2011)

The possible molecular evolution of sapoviruses by inter- and intra-genogroup recombination - Karoline dos Anjos; Lidia M. P. Lima; Paula Andreia Silva; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2011)

Molecular and biological characterization of a new Brazilian begomovirus, euphorbia yellow mosaic virus (EuYMV), infecting Euphorbia heterophylla plants - Fernanda R. Fernandes; Leonardo C. Albuquerque; Cristiane L. de Oliveira; Andréa R. R. Cruz; Wesley B. da Rocha; Talita G. Pereira; Fernanda Y. B. Naito; Natália de M. Dias; Tatsuya Nagata; Josias C. Faria; Francisco M. Zerbini; Francisco J. L. Aragão; et al. (Archives of Virology, 2011)

Search in Solanum (section Lycopersicon) germplasm for sources of broad-spectrum resistance to four Tospovirus species - É. C. Dianese; M. E. N. Fonseca; A. K. Inoue-Nagata; R. O. Resende; L. S. Boiteux (Euphytica, 2011)

Two methods of temperature control for single-molecule measurements - Matthew A. B. Baker; Yuichi Inoue; Kuniaki Takeda; Akihiko Ishijima; Richard M. Berry (European Biophysics Journal, 2011)

Potential for spectral indices to remotely sense phosphorus and potassium content of legume-based pasture as a means of assessing soil phosphorus and potassium fertility status - K. Kawamura; A. D. Mackay; M. P. Tuohy; K. Betteridge; I. D. Sanches; Y. Inoue (International Journal of Remote Sensing, 2011)

Audit and improve! Evaluation of a real-time probe-based PCR assay with internal control for the direct detection of Mycobacterium tuberculosis complex - M. Inoue; W. Y. Tang; S. Y. Wee; T. Barkham (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Isolation and characterization of 17 polymorphic microsatellite loci in the spectaclecase, Cumberlandia monodonta (Bivalvia: Margaritiferidae) - Kentaro Inoue; Gregory R. Moyer; Ashantyé Williams; Emy M. Monroe; David J. Berg (Conservation Genetics Resources, 2011)

Enhanced Inhibitory Effects of TBT Chloride on the Development of F1 Rats - H. Asakawa; M. Tsunoda; T. Kaido; M. Hosokawa; C. Sugaya; Y. Inoue; Y. Kudo; T. Satoh; H. Katagiri; H. Akita; M. Saji; M. Wakasa; et al. (Archives of Environmental Contamination and Toxicology, 2010)

Colony growth and reproductive ability of feral nests of the introduced bumblebee Bombus terrestris in northern Japan - M. N. Inoue; J. Yokoyama; K. Tsuchida (Insectes Sociaux, 2010)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Effects of nimesulide, a cyclooxygenase-2 selective inhibitor, on colitis induced tumors - T. Inoue; I. Hirata; M. Murano (Inflammopharmacology, 2008)

Natural infection of Alternanthera tenella (Amaranthaceae) by a new potyvirus - A. M. R. Almeida; C. Y. Fukushigue; F. Sartori; E. Binneck; S. R. R. Marin; A. K. Inoue-nagata; C. M. Chagas; E. R. Souto; T. Mituti (Archives of Virology, 2007)

Identification and characterization of RNA-dependent RNA polymerase activity in recombinant Japanese encephalitis virus NS5 protein - F. Yu; F. Hasebe; S. Inoue; E. G. M. Mathenge; K. Morita (Archives of Virology, 2007)

Evolutionary trend of phylogenetic diversity of nitrogen fixation genes in the gut community of wood‐feeding termites - A. YAMADA; T. INOUE; S. NODA; Y. HONGOH; M. OHKUMA (Molecular Ecology, 2007)
Nitrogen fixation by gut microorganisms is one of the crucial aspects of symbiosis in wood‐feeding termites since these termites thrive on a nitrogen‐poor diet. In order to understand the evolution of this symbiosis, we analysed the nitrogenase structural gene nifH in the gut microbial communities. In conjunction with the published sequences, we compared approximately 320 putatively functional NifH protein sequences obtained from a total of 19 termite samples that represent all the major branches of their currently proposed phylogeny, and from one species of the cockroach Cryptocercus that shares a common ancestor with termites. Using multivariate techniques for clustering and ordination, a phylogeny of NifH protein sequences was created and plotted variously with host termite families, genera, and species. Close concordance was observed between NifH communities and the host termites at genus level, but family level relationships were not always congruent with accepted termite clade structure. Host groups examined included basal families (Mastotermitidae, Termopsidae, Kalotermitidae, as well as Cryptocercus ), the most derived lower termite family Rhinotermitidae, and subfamilies representing the advanced and highly diverse apical family Termitidae (Macrotermitinae, Termitinae, and Nasutitermitinae). This selection encompassed the major nesting and feeding styles recognized in termites, and it was evident that NifH phylogenetic divergence, as well as the occurrence of alternative nitrogenase‐type NifH, was to some extent dependent on host lifestyle as well as phylogenetic position.

Changes in blood flow in a conduit artery and superficial vein of the upper arm during passive heating in humans - Anna Ooue; Tomoko Ichinose-Kuwahara; A. K. M. Shamsuddin; Yoshimitsu Inoue; Takeshi Nishiyasu; Shunsaku Koga; Narihiko Kondo (European Journal of Applied Physiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cospeciation in the triplex symbiosis of termite gut protists ( Pseudotrichonympha spp.), their hosts, and their bacterial endosymbionts - S. NODA; O. KITADE; T. INOUE; M. KAWAI; M. KANUKA; K. HIROSHIMA; Y. HONGOH; R. CONSTANTINO; V. UYS; J. ZHONG; T. KUDO; M. OHKUMA (Molecular Ecology, 2007)
A number of cophylogenetic relationships between two organisms namely a host and a symbiont or parasite have been studied to date; however, organismal interactions in nature usually involve multiple members. Here, we investigated the cospeciation of a triplex symbiotic system comprising a hierarchy of three organisms — termites of the family Rhinotermitidae, cellulolytic protists of the genus Pseudotrichonympha in the guts of these termites, and intracellular bacterial symbionts of the protists. The molecular phylogeny was inferred based on two mitochondrial genes for the termites and nuclear small‐subunit rRNA genes for the protists and their endosymbionts, and these were compared. Although intestinal microorganisms are generally considered to have looser associations with the host than intracellular symbionts, the Pseudotrichonympha protists showed almost complete codivergence with the host termites, probably due to strict transmissions by proctodeal trophallaxis or coprophagy based on the social behaviour of the termites. Except for one case, the endosymbiotic bacteria of the protists formed a monophyletic lineage in the order Bacteroidales, and the branching pattern was almost identical to those of the protists and the termites. However, some non‐codivergent evolutionary events were evident. The members of this triplex symbiotic system appear to have cospeciated during their evolution with minor exceptions; the evolutionary relationships were probably established by termite sociality and the complex microbial community in the gut.

Evaluation of snow/ice albedo parameterizations and their impacts on sea ice simulations - Jiping Liu; Zhanhai Zhang; Jun Inoue; Radley M. Horton (International Journal of Climatology, 2007)
Climate models use a variety of snow/ice albedo parameterizations for the ice covered ocean. In this study, we applied in situ measurements (surface temperature, snow depth and ice thickness) obtained from the Surface Heat Budget of the Arctic Ocean (SHEBA) as input values to four different snow/ice albedo parameterizations (representing the spectrum of parameterizations used in stand‐alone sea ice models, numerical weather prediction and regional climate models of the Arctic Basin, and coupled global climate models), and evaluated the parameterized albedos against the SHEBA observed albedo. Results show that these parameterizations give very different representations of surface albedo. The impacts of systematic biases in the input values on the parameterized albedos were also assessed. To further understand how sea ice processes are influenced by differences in the albedo parameterizations, we examined baseline sea ice characteristics and responses of sea ice to an external perturbation for the simulations of the albedo parameterizations using a stand‐alone basin‐scale dynamic/thermodynamic sea ice model. Results show that an albedo treatment of sufficient complexity can produce more realistic basin‐scale ice distributions, and likely more realistic ice responses as climate warms. Copyright © 2006 Royal Meteorological Society

Synchrotron IR study of hydrous ringwoodite (γ-Mg2SiO4) up to 30 GPa - E. M. Chamorro Pérez; I. Daniel; J.-C. Chervin; P. Dumas; J. D. Bass; T. Inoue (Physics and Chemistry of Minerals, 2006)

The Monitoring of Insects to Maintain Biodiversity in Ogawa Fores Reserve - S. Makino; H. Goto; T. Inoue; M. Sueyoshi; K. Okabe; M. Hasegawa; K. Hamaguchi; H. Ctanaka; I. Okochi (Environmental Monitoring and Assessment, 2006)

Intracolony variation of bacterial gut microbiota among castes and ages in the fungus‐growing termite Macrotermes gilvus - Y. HONGOH; L. EKPORNPRASIT; T. INOUE; S. MORIYA; S. TRAKULNALEAMSAI; M. OHKUMA; N. NOPARATNARAPORN; T. KUDO (Molecular Ecology, 2006)
The fungus‐growing termites Macrotermes cultivate the obligate ectosymbiontic fungi, Termitomyces . While their relationship has been extesively studied, little is known about the gut bacterial symbionts, which also presumably play a crucial role for the nutrition of the termite host. In this study, we investigated the bacterial gut microbiota in two colonies of Macrotermes gilvus , and compared the diversity and community structure of bacteria among nine termite morphotypes, differing in caste and/or age, using terminal restriction fragment length polymorphism (T‐RFLP) and clonal analysis of 16S rRNA. The obtained molecular community profiles clustered by termite morphotype rather than by colony, and the clustering pattern was clearly more related to a difference in age than to caste. Thus, we suggest that the bacterial gut microbiota change in relation to the food of the termite, which comprises fallen leaves and the fungus nodules of Termitomyces in young workers, and leaves degraded by the fungi, in old workers. Despite these intracolony variations in bacterial gut microbiota, their T‐RFLP profiles formed a distinct cluster against those of the fungus garden, adjacent soil and guts of sympatric wood‐feeding termites, implying a consistency and uniqueness of gut microbiota in M. gilvus . Since many bacterial phylotypes from M. gilvus formed monophyletic clusters with those from distantly related termite species, we suggest that gut bacteria have co‐evolved with the termite host and form a microbiota specific to a termite taxonomic and/or feeding group, and furthermore, to caste and age within a termite species.

Assessment of room temperature influence on finger blood flow response induced by short-term grasping of vibrating handle - M. H. Mahbub; M. Inoue; K. Yokoyama; M. S. Laskar; H. Ohnari; K. Suizu; J. Inagaki; Y. Takahashi; N. Harada (International Archives of Occupational and Environmental Health, 2006)

High prevalence of hepatitis B, C and delta virus infections among blood donors in Mongolia - B. Tsatsralt-Od; M. Takahashi; T. Nishizawa; J. Inoue; D. Ulaankhuu; H. Okamoto (Archives of Virology, 2005)

Comparison of Expression of Glucokinase Gene and Activities of Enzymes Related to Glucose Metabolism in Livers between Dog and Cat - A. Tanaka; A. Inoue; A. Takeguchi; T. Washizu; M. Bonkobara; T. Arai (Veterinary Research Communications, 2005)

Effect of room temperature on percentage finger systolic blood pressure response to finger cooling - M. S. Laskar; K. Ohmura; M. Inoue; K. Yokoyama; J. Inagaki; Y. Takahashi; M. H. Mahbub; H. Ohnari; N. Harada (European Journal of Applied Physiology, 2005)

Sundasalanx (Sundasalangidae) is a progenetic clupeiform, not a closely‐related group of salangids (Osmeriformes): mitogenomic evidence - N. B. Ishiguro; M. Miya; J. G. Inoue; M. Nishida (Journal of Fish Biology, 2005)
Partitioned Bayesian analysis of whole mitochondrial genome sequences from 30 basal teleosts confidently placed Sundasalanx (Sundasalangidae) within the Clupeiformes, not Osmeriformes as originally thought. This study represents the first demonstration of the phylogenetic position of Sundasalanx on a phylogenetic tree.

Effect of skin temperature on the ion reabsorption capacity of sweat glands during exercise in humans - A. K. M. Shamsuddin; T. Kuwahara; A. Oue; C. Nomura; S. Koga; Y. Inoue; N. Kondo (European Journal of Applied Physiology, 2005)

Findings through the AsiaFlux network and a view toward the future - S. Yamamoto; N. Saigusa; M. Gamo; Y. Fujinuma; G. Inoue; T. Hirano (Journal of Geographical Sciences, 2005)

A novel melon flexivirus transmitted by whitefly - T. Nagata; D. M. T. Alves; A. K. Inoue-Nagata; T.-Y. Tian; E. W. Kitajima; J. E. Cardoso; A. C. de vila (Archives of Virology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Characterization of Oita virus 296/1972 of Rhabdoviridae isolated from a horseshoe bat bearing characteristics of both lyssavirus and vesiculovirus - K. Tanaka; Y. Sato; S. Morikawa; D. Hayasaka; M. Moriyama; T. Ono; A. Yamada; T. Kurata; T. Iwasaki; S. Inoue; S. Kanai (Archives of Virology, 2004)

Genetic approach to sleep-disordered breathing - Hiroshi KADOTANI; M TANIGUCHI; Y TAKAHASHI; Y INOUE (Sleep and Biological Rhythms, 2004)

Augmented cytoplasmic Smad4 induces acceleration of TGF-?1 signaling in renal tubulointerstitial cells of hereditary nephrotic ICGN mice with chronic renal fibrosis; possible role for myofibroblastic differentiation - Y. Goto; N. Manabe; K. Uchio-Yamada; M. Yamaguchi-Yamada; N. Inoue; Y. Yamamoto; A. Ogura; N. Nagano; H. Miyamoto (Cell and Tissue Research, 2004)

Tandem duplication of alkaline phosphatase genes and polymorphism in the intergenic sequence in Bombyx mori - M. Itoh; T. Inoue; Y. Kanamori; S. Nishida; M. Yamaguchi (Molecular Genetics and Genomics, 2003)

The effects of histamine on the lipopolysaccharide-induced metallothionein-I mRNA expression in the mouse spleen - T. Inoue; M. Nakano; N. Oda; T. Yoneyama; Y. Okano; K. Onodera; H. Furuta; C. A. Sogawa; N. Sogawa (Inflammation Research, 2003)

Nucleotide sequences of the coat protein gene of potyviruses infecting Ornithogalum thyrsoides - S. Fuji; M. Inoue; H. Yamamoto; H. Furuya; H. Naito; T. Matsumoto (Archives of Virology, 2003)

Pepper yellow mosaic virus, a new potyvirus in sweetpepper, Capsicum annuum - A. K. Inoue-Nagata; M. E. N. Fonseca; R. O. Resende; L. S. Boiteux; D. C. Monte; A. N. Dusi; A. C. de ávila; R. A. A. van der Vlugt (Archives of Virology, 2002)

Complete nucleotide sequence of the genomic RNA of Aconitum latent virus (genus Carlavirus) isolated from Delphinium sp. - S. Fuji; H. Yamamoto; M. Inoue; K. Yamashita; Y. Fukui; H. Furuya; H. Naito (Archives of Virology, 2002)

Effect of MS-153 on the development of behavioral sensitization to locomotion- and ataxia-inducing effects of phencyclidine - Abekawa T.; Honda M.; Ito K.; Inoue T.; Koyama T. (Psychopharmacology, 2002)

Genetic identification of two distinct DNA polymerases, DnaE and PolC, that are essential for chromosomal DNA replication in Staphylococcus aureus - R. Inoue; C. Kaito; M. Tanabe; K. Kamura; N. Akimitsu; K. Sekimizu (Molecular Genetics and Genomics, 2001)

Evaluation of formation potential of trihalomethanes and mutagens due to chlorination of river water along the Kizu River in the Yodo River system in Japan - S. Sanukida; T. Nobukawa; M. Ichihara; H. Shima; K. Inoue; S. Nakachi (Limnology, 2001)

Relationships among Nicotiana species revealed by the 5S rDNA spacer sequence and fluorescence in situ hybridization - S. Kitamura; M. Inoue; N. Shikazono; A. Tanaka (Theoretical and Applied Genetics, 2001)

Karyotype analysis of Nicotiana kawakamii Y. Ohashi using DAPI banding and rDNA FISH - R. Nakamura; S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2001)

Diverse genes of cellulase homologues of glycosyl hydrolase family 45 from the symbiotic protists in the hindgut of the termite Reticulitermes speratus - Kuniyo Ohtoko; M. Ohkuma; Shigeharu Moriya; Tetsushi Inoue; Ron Usami; Toshiaki Kudo (Extremophiles, 2000)

Quantitative chromosome maps and rDNA localization in the T subgenome of Nicotiana tabacum L. and its putative progenitors - S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2000)

Determination of the phase boundary between ilmenite and perovskite in MgSiO 3 by in situ X-ray diffraction and quench experiments - K. Kuroda; T. Irifune; T. Inoue; N. Nishiyama; M. Miyashita; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2000)

Hematite in pyrophyllite ore deposits, Shobara district, southwestern Japan - M. Ohkawa; Y. Yamashita; M. Inoue; R. Kitagawa; S. Takeno (Mineralogy and Petrology, 2000)

Subsite-specific risk factors for hypopharyngeal and esophageal cancer (Japan) - T. Takezaki; M. Shinoda; S. Hatooka; Y. Hasegawa; S. Nakamura; K. Hirose; M. Inoue; N. Hamajima; T. Kuroishi; H. Matsuura; K. Tajima (Cancer Causes & Control, 2000)

Two novel mutations of SURF1 in Leigh syndrome with cytochrome c oxidase deficiency - M. Teraoka; Y. Yokoyama; S. Ninomiya; C. Inoue; S. Yamashita; Y. Seino (Human Genetics, 1999)

Two novel mutations of SURF1 in Leigh syndrome with cytochrome c oxidase deficiency - M. Teraoka; Y. Yokoyama; S. Ninomiya; C. Inoue; S. Yamashita; Y. Seino (Human Genetics, 1999)

Effects of N-nitrosodimethylamine (NDMA) on the oxidative status of rat liver - M. Taniguchi; A. Yasutake; K. Takedomi; K. Inoue (Archives of Toxicology, 1999)

PCR-based method for identifying the S-genotypes of Japanese pear cultivars - T. Ishimizu; K. Inoue; M. Shimonaka; T. Saito; O. Terai; S. Norioka (Theoretical and Applied Genetics, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Reduced glutathione promotes callus growth and shoot development in a shoot tip culture of apple root stock M26 - K. Nomura; S. Matsumoto; K. Masuda; M. Inoue (Plant Cell Reports, 1998)

Short communicationRecovery from derangement of natural killer‐like activity of leucocytes due to Zn or Mn deficiency in rainbow trout, Oncorhynchus mykiss (Walbaum), by the oral administration of these elements - M Inoue; S Satoh; M Maita; V Kiron; N Okamoto (Journal of Fish Diseases, 1998)

Histopathological Changes Within the Testis Caused by Allyl Chloride Exposure in Mice - M. Zhao; M. Omura; S. Tokunaga; Y. Romero; N. Inoue (Bulletin of Environmental Contamination and Toxicology, 1998)

Tea and coffee consumption and the risk of digestive tract cancers: data from a comparative case-referent study in Japan - M. Inoue; K. Tajima; K. Hirose; N. Hamajima; T. Takezaki; T. Kuroishi; S. Tominaga (Cancer Causes & Control, 1998)

Genetic studies of the leptin receptor gene in morbidly obese French Caucasian families - Stephan Francke; Karine Clement; Christian Dina; Hiroshi Inoue; Philip Behn; Vincent Vatin; Arnaud Basdevant; Bernard Guy-Grand; M. Alan Permutt; Philippe Froguel; J. Hager (Human Genetics, 1997)

Pyruvate alleviates toxic effects of ethanol on cells in culture - K. Fukaya; M. Miyazaki; H. Pu; B. Katayama; Y. Inoue; R. Ohashi; C. Nakamura; M. Namba (Archives of Toxicology, 1997)

Cyclooxygenase inhibitors enhance the production of tissue inhibitor-1 of metalloproteinases (TIMP-1) and pro-matrix metalloproteinase 1 (proMMP-1) in human rheumatoid synovial fibroblasts - S. Takahashi; T. Inoue; M. Higaki; Y. Mizushima (Inflammation Research, 1997)

Prolactin-like immunoreactivity in the granules of neural complex cells in the ascidian Halocynthia roretzi - M. Ogawa; K. Inoue; S. Kikuyama; K. Terakado; K. Yamamoto (Cell and Tissue Research, 1997)

Interaction between carbamazepine and bromperidol - K. Otani; M. Ishida; N. Yasui; T. Kondo; K. Mihara; A. Suzuki; H. Furukori; S. Kaneko; Y. Inoue (European Journal of Clinical Pharmacology, 1997)

Restriction endonuclease mapping and molecular cloning of the human herpesvirus 6 variant B strain Z29 genome - G. J. Lindquester; N. Inoue; R. D. Allen; J. W. Castelli; F. R. Stamey; T. R. Dambaugh; J. J. O'Brian; R. M. Danovich; N. Frenkel; P. E. Pellett (Archives of Virology, 1996)

On the parameter estimation for diffusion models of single neuron's activities - Junko Inoue; Shunsuke Sato; Luigi M. Ricciardi (Biological Cybernetics, 1995)

On the parameter estimation for diffusion models of single neuron?s activities - Junko Inoue; Shunsuke Sato; Luigi M. Ricciardi (Biological Cybernetics, 1995)

Dynamics of swidden agriculture in East Kalimantan - Makoto Inoue; Abubakar M. Lahjie (Agroforestry Systems, 1990)

Characterization of the beta-lactamase from Klebsiella pneumoniae - E. E. Stobberingh; R. Okamoto; M. Inoue; S. Mitsuhashi (Antonie van Leeuwenhoek, 1985)

Antigenic difference between intracellular and membrane antigens induced by herpesvirus of turkeys - M. Inoue; T. Mikami; H. Kodama; M. Onuma; H. Izawa (Archives of Virology, 1980)